Design and Development of Tempe Fermentation Tool Based on Fuzzy Method to Determine Tempe Maturity Level - Hanoum, Nur Anisza; Villaverde, Korrine; Saputra, Yoga; Nuhuyeva, Åəhla; Ye, Tian (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study aims to design an innovative tempeh fermentation tool based on the Mamdani fuzzy method that is able to accelerate fermentation and determine the level of tempeh maturity accurately using weight parameters and visual image analysis. This tool is designed to improve the efficiency, productivity, and competitiveness of the tempeh industry by maintaining the quality of tempeh according to standards. Methodology: The results showed that this tool was able to accelerate fermentation with an average time of 21.7 hours, producing quality tempeh with evenly growing fungi without rot. The load cell sensor successfully weighed two tempeh at once with an average weight loss of 10.5 grams, and the ESP32CAM successfully monitored the tempeh visually during fermentation. Main Findings: From the results testing that has been done for 4× shows that tool This succeed speed up fermentation with eat average time 21.7 hours with criteria mold grow even and not rotten and loadcell sensor successful Weigh 2 tempeh at a time fermented with decline average weight 10.5 grams and ESP32CAM successfully monitored tempeh visually at the time fermented . Novelty/Originality of this study: The novelty of this research lies in the integration of DHT11 sensor technology, load cells, and ESP32CAM which enables automatic control of temperature and humidity, real-time monitoring, and accurate determination of tempeh maturity levels. This innovation provides a practical solution to improve the efficiency of the fermentation process and the quality of tempeh production, making it suitable for application on an industrial scale.